Front Cover: Design and Synthesis of Porous Coordination Polymers with Expanded One‐Dimensional Channels and Strongly Lewis‐Acidic Sites (ChemNanoMat 1/2018). Issue 1 (13th December 2017) - Kajiwara, Takashi; Higashimura, Hideyuki; Higuchi, Masakazu; Kitagawa, Susumu
Abstract : Porous coordination polymers (PCPs) that consist of La III cations and thiophene‐based tritopic organic linkers were synthesized and structurally characterized to have the same type of one‐dimensional hexagonal channels, but with thiophene rings at different positions. The La III cations (light blue, highlighted) showed, after removal of the coordinated solvent, strong Lewis acidity to catalyze the cyanosilylation of carbonyl compounds. The highest catalytic activity was observed for the La‐PCP with the largest channels, indicating enhanced diffusion of substrates/products (pink and green balls) into the channels. More information can be found in the Full Paper by Susumu Kitagawa et al. onpage 104 in Issue 1, 2018 (DOI:10.1002/cnma.201700256 ).